A mixed‐method systematic review: support for ethical competence of nurses. (19th July 2013) - Poikkeus, Tarja; Numminen, Olivia; Suhonen, Riitta; Leino‐Kilpi, Helena
Abstract Aim The aim was to appraise and synthesize evidence of empirical studies of how nurses' ethical competence can be supported. Background Ethical competence is an essential element of nursing practice. Nurses increasingly need support in competence when carrying out their responsibilities towards their patients. Design A mixed‐method systematic review of quantitative and qualitative studies was undertaken according to the University of York's Centre for Reviews and Dissemination guidelines. Data sources Searches of MEDLINE, Nursing Database and British Nursing Index databases were conducted, yielding 512 citations between 1985–2012. Methods After a two‐stage application of inclusion and exclusion criteria, 34 articles were included. The quality of the studies was assessed using STROBE or COREQ criteria. Data were analysed by content analysis. Results Nurses' ethical competence has been studied from different viewpoints: ethical decision‐making, ethical sensitivity, ethical knowledge and ethical reflection. There was little empirical evidence of provided support, but studies offered recommendations on how to support ethical competence. The most common strategies to support ethical competence were ethics education, ethics rounds, ethics committee and consultation. Nurse leaders and colleagues have a key role in providing opportunities for nurses to gain ethical competence. Conclusions There is a need to develop evidence‐based support at the organizational and individual level to support nurses' ethical competence. Barriers for multiprofessional cooperation in ethical issues should be recognized and addressed as part of the development of organizational ethical practices. Research should pay more attention to the conceptual, theoretical and practical perspectives of ethical competence.